2021
DOI: 10.1093/asj/sjab425
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Percutaneous Intraarterial Facial/Supratrochlear Arterial Hyaluronidase Injection for Treatment of Vascular Embolism Resulting From Hyaluronic Acid Filler Cosmetic Injection

Abstract: Background Vascular embolism is a serious complication of hyaluronic acid (HA) filler cosmetic injection and hyaluronidase injection has been proposed as the treatment. Until now there is a lack of adequate clinical evidence regarding the benefits of treatment for HA filler-induced vascular embolism by percutaneous facial or supratrochlear arterial hyaluronidase injection. Objectives To evaluate the efficacy of percutaneous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Extravascular hyaluronidase was found to be most effective when given early (within 4 h), at high doses, and distributed over multiple treatment sessions [ 174 , 204 ]. Similarly, intravascular hyaluronidase was effective in the treatment of FIVO in the rabbit ear model, especially if injected within the first 4 h post injury, as well as in humans for the treatment of ischemic skin injuries [ 205 , 206 ].…”
Section: Pathophysiology Of Ha-mediated Vascular Occlusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extravascular hyaluronidase was found to be most effective when given early (within 4 h), at high doses, and distributed over multiple treatment sessions [ 174 , 204 ]. Similarly, intravascular hyaluronidase was effective in the treatment of FIVO in the rabbit ear model, especially if injected within the first 4 h post injury, as well as in humans for the treatment of ischemic skin injuries [ 205 , 206 ].…”
Section: Pathophysiology Of Ha-mediated Vascular Occlusionmentioning
confidence: 99%
“…Hyaluronidase therapy should be initiated promptly (ideally within the first 4 h post-injury), employ high doses, and be performed over multiple sessions spaced regularly over the first 24–48 h [ 119 , 146 ]. Treatment should immediately target underperfused regions demonstrating delayed capillary refill as well as any suspected sites of main arterial occlusion [ 150 , 174 , 206 ].…”
Section: Pathophysiology Of Ha-mediated Vascular Occlusionmentioning
confidence: 99%
“…[14][15][16] However, emboli-induced skin necrosis and ptosis usually show a better prognosis after appropriate treatment. 17,18 Only a few cases of severe necrosis can be treated using full-thickness skin grafts. 15 In addition to ordinary fillers, we found that lidocaine and adrenaline solutions can induce intravascular embolisms and ultimately elicit blindness.…”
Section: Discussionmentioning
confidence: 99%
“…It dissolves subcutaneous nodules and degrades HA correcting excessive quantities of injected HA fillers [41][42][43][44][45] and its duration of the activity is about 24-48 h in dermal tissues [10]. It can be used at a high dose of 200 U or higher for treating skin necrosis associated with HA filler injections, caused by vascular occlusion and sometimes intra-arterially as a thrombolytic to treat eye/intracranial complications [16], and often without hypersensitivity test [23].…”
Section: Mechanism Of Action and Therapeutic Uses Of Hyaluronidasementioning
confidence: 99%
“…Similarly, no evidence was found, in a form of RCTs, clinical trials, and retrospective case-control studies, on the management of over-corrections, inflammatory nodules, or tissue ischemia/necrosis associated with aesthetic HA filler injections; the available evidence was mainly retrospective case reports or case series. We have also listed the summary of 11 excluded studies [10,14,16,[56][57][58][59][60][61][62][63] in table 5. They were retrospective case series, with 5 cases or more, reporting on the use of hyaluronidase for managing aesthetic complications associated with aesthetic HA filler injection.…”
Section: Effectiveness Of Hyaluronidase For Management Of Over-correc...mentioning
confidence: 99%